Gender differences in wage expectations: the role of biased beliefs - Stephanie Briel; Aderonke Osikominu; Gregor Pfeifer; Mirjam Reutter; Sascha Satlukal (Empirical Economics, 2021)
We analyze gender differences in expected starting salaries along the wage expectations distribution of prospective university students in Germany, using elicited beliefs about both own salaries and salaries for average other students in the same field. Unconditional and conditional quantile regressions show 5–15% lower wage expectations for females. At all percentiles considered, the gender gap is more pronounced in the distribution of expected own salary than in the distribution of wages expected for average other students. Decomposition results show that biased beliefs about the own earnings potential relative to others and about average salaries play a major role in explaining the gender gap in wage expectations for oneself.
Keywords: J16; D84; D91; C21; 330; Gender pay gap; Wage expectations; Biased beliefs; Decomposition analysis; Conditional quantile regression; Unconditional quantile regression (RIF regression)